Electrokinetic Remediation of PPCPs in Soil: Effect of operating parameters - Lopes, Vanda Varela (2018)
Reclaimed wastewater is an important source of water that complements the fragile and limited natural water sources, being widely used for irrigation of agricultural land, particularly in arid and semi-arid regions. Considerable levels of pharmaceuticals and personal care products (PPCPs), are found in effluents and in land fields irrigated with these “recycled waters”. Once in the soil, plants have the capacity to uptake, translocate and accumulate these compounds of emerging concern (CECs) in the edible parts of food crops. These can subsequently enter the food chain. This is of concern as some of these compounds act as endocrine disruptors. The main objective of the present dissertation was to study and develop the electrokinetic process to promote CECs degradation using an agricultural soil as matrix. The developed technology was evaluated in terms of remediation efficiency and sustainability. For that, the soil was spiked with a 16 mg/kg solution containing five CECs. The selected compounds were: sulfamethoxazole (SMX), ibuprofen (IBU), triclosan (TCS), caffeine (CAF) and atenolol (ATN). The feasibility of the electrokinetic (EK) process was evaluated by testing different operating modes, using graphite rods as electrodes. The main tested operating modes were: current intensity (CI); ON/OFF switch intervals (Sw); and reversed electro-polarization intervals (RP). For CI mode, 100, 50 and 10 mA were tested, for 24h ON in the case of CI-10 and 24h ON/OFF for CI-100 and CI-50. For Sw and RP systems (performed at 10 mA), periods of 6, 12 and 24h were tested. All experiments were carried out for a 7 day period, in a lab scale microcosms. Additionally, two complementary reference testes were done: initial control and control after 7 days, both without direct current (DC) electric field. Experiment CI-50 showed high degrading percentages for some compounds (97 ± 8% of SMX and 61 ± 5% of IBU), but the electrodes were unstable and presented high signs of corrosion after 24h of 50 mA application. Experiment CI-10 presented the highest degrading percentage of TCS (56 ± 0%), but a significant soil pH gradient was observed (6.8-11.2). The results with periodic current application of 12h (Sw system) showed to be the most viable option for achieving the CECs degradation without submitting the soil to extreme physico-chemical changes. Removal efficiencies in experiment Sw-12h ranged between 36 and 72% (with RSD from 0 to 10%). Although. In this system, the electrolysis of water produced a subtle pH gradient. The slight physico-chemical changes promoted in the soil, may have enabled, to some extent, the solubilization and/or mobilization of contaminants under study. This may have enhanced the degradation of contaminants by two remediation mechanisms: (i) electrochemical degradation and (ii) bioremediation. The EK process shows to be a sustainable option for the remediation of CECs in clay soils, thus decreasing the environmental and humans associated risks.